Studi Perspektif Masyarakat untuk Program Restorasi Ekosistem Hutan Mangrove (Studi Kasus Masyarakat Desa Bogak Kecamatan Tanjung Tiram Kabupaten Batu Bara) - Jeprianto Manurung; Mohammad Basyuni; Oding Affandi (Peronema Forestry Science Journal, 2012)
Studies on restoration program has been implemented in many countries which have mangrove forest. This research was design on perspective community based of Bogak villagers in it’s correction to mangrove degradation and it’s existence  to social, economy and culture.  The  questionnaire was employed to analyze data using quantitative  descriptive method. This research was carried out from June 2011 to March 2012. The aim of research was to study the specific condition of mangrove forest in relation to indigenous people. The result showed that 86.97% of respondents knew very well about mangrove forest, 97.32% of respondents understood the functions of mangrove forest. They were active to response in the restoration program (97.32%) and 83.52% were willing to participate in restoration program. In this study mangrove nursery was useful due to give community a direct example how to restore mangrove well.. Key words: Mangrove restoration, perspective of villagers. restoration program